Be Present: Mapping Emotional Presence and Perceived Value of Attendance through a 10-Day Digital Diary - Esperança, M. B.; Ferreira, A.I.; Santana, P.; Mariano, P. (3rd Meeting of the International Attendance Behaviour Network, 2025)
Presenteeism—being physically present at work while mentally or emotionally disengaged—is increasingly recognised as a critical challenge for organisational performance and employee well-being. Traditional approaches have focused on structural or health-related cause predictors, but there is limited insight into how workers experience presenteeism on a daily basis, and how they evaluate its short- and long-term consequences. This paper presents Be Present, a mobile application developed as a research tool to monitor workers’ presence at work and perceived value of their attendance over a 10-day period. The app invites users to reflect briefly on their physical and emotional health at the beginning and end of each workday. It collects contextual data – job autonomy, stress, workload, physical discomfort -, while also captures how beneficial it was for users—and for their organisation—to have attended work that day, in the short, medium, and long term. Rather than functioning as an intervention, Be Present serves as a self-monitoring diary that enables to capture nuanced patterns of presence at work. It combines subjective experience with behavioural context, offering a rich dataset for understanding how emotional and physical states fluctuate in real-life settings and how these are connected to perceptions of contribution and value. Preliminary feedback highlights user engagement and the potential of the tool to raise awareness around presenteeism while generating actionable insights. This paper will outline the conceptual basis, methodological approach, and early findings of Be Present, opening space for discussion on how digital tools can enhance our understanding of presence, motivation, and well-being in the modern workplace.